Cascaded Internal Phase Control of All-Fiber Coherent Fiber Laser Array - Chang, Hongxiang; Su, Rongtao; Zhang, Yuqiu; Jiang, Min; Chang, Qi; Long, Jinhu; Ma, Pengfei; Ma, Yanxing; Zhou, Pu (Frontiers in Physics, 2022)
Fiber lasers have been widely used in medical care, industry, and scientific research in recent years. Coherent beam combining of fiber lasers with internal phase control has drawn many interests at present, which is a promising method to achieve large scale optical phased array. In this paper, we present a cascaded internal phase control method to expand the internal all-fiber phased array. The method distributes the phase measurements to a series of internal Mach-Zender interferometers. Then the phase of each loop is locked by gradient descent algorithm. Electric control method to compensate π-ambiguity between channels is proposed. Finally, phases of three fiber beams are locked experimentally to verify the feasibility of the method and the residue phase error is better than λ/22.